2021
DOI: 10.3390/atmos12091137
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of the COVID-19 Lockdown and Regional Fire on the Air Quality of Medellín, Colombia

Abstract: Governments’ responses to the COVID-19 pandemic provide a unique opportunity to study the effects of restricted socioeconomic activity on air quality. Here, we study the changes in air pollution levels during the lockdown in Medellín and its metropolitan area, Colombia, for periods with and without enhanced regional fire activity, considering the effects of meteorology using random forest and multiple linear regression methods. The lockdown measures, which reduced mean traffic volume by 70% compared to 2016–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…In Figure 5, for NO x , there is a behavior similar to the one observed with PM 2.5 . The reduction of this pollutant can be explained for similar reasons we highlighted above for PM 2.5 (Henao et al, 2021). For PM 2.5 , a significant reduction is observed from March 31st and for NO x earlier on March 16th.…”
Section: Analysis Of the Impact On Pollutant Concentrationssupporting
confidence: 70%
See 1 more Smart Citation
“…In Figure 5, for NO x , there is a behavior similar to the one observed with PM 2.5 . The reduction of this pollutant can be explained for similar reasons we highlighted above for PM 2.5 (Henao et al, 2021). For PM 2.5 , a significant reduction is observed from March 31st and for NO x earlier on March 16th.…”
Section: Analysis Of the Impact On Pollutant Concentrationssupporting
confidence: 70%
“…These results are consistent with other studies performed in the Aburrrá Valley that showed a reduction in the PM 2.5 concentrations during the lockdown. This reduction can be attributed to the traffic reduction due this particles are mainly formed by particulate matter re-suspension associated to vehicles emissions (Henao et al, 2021;Mendez-Espinosa et al, 2020); industrial activities should contribute far less than transportation, which accounts for the majority of emissions (more than 80% of PM and NO x ) (AMVA & Bolivariana, 2017). Similar reductions were reported worldwide due to the lockdown and restrictions on transportation, economic, and social activities (Chauhan & Singh, 2020;Gkatzelis et al, 2021;Venter, Aunan, Chowdhury, & Lelieveld, 2020).…”
Section: Analysis Of the Impact On Pollutant Concentrationsmentioning
confidence: 99%
“…Not only have been carried out a few studies in Latin American countries like the ones in Northern South America but also those studies have not considered the analysis after the lockdown (i.e., post-lockdown, to our knowledge) (Mendez-Espinosa et al 2020 ; Arregocés et al 2021 ; Henao et al 2021 ; Sokhi et al 2021 ). Mendez-Espinosa et al ( 2020 ) found reductions in NO 2 (28–65%), PM 10 (37–66%), and PM 2.5 (45–76%) related to lockdown restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Henao et al ( 2021 ) identified that in a single city in Colombia, large average reductions in PM 2.5 (50–63%), PM 10 (59–64%), NO (43–47%), NO 2 (43–47%), and CO (40–47%), and increments in O 3 (19–22%), were presented. Their comparisons of lockdown with pre-lockdown periods used multivariate regression analysis methods, and machine learning (random forest) to untangle the effects of the lockdown on pollution levels.…”
Section: Introductionmentioning
confidence: 99%